MedIoT-LAP: Secure and efficient lightweight AEAD-Based authentication protocol for medical IoT - Muhammad Tanveer; Saud Alhajaj Aldossari (Ain Shams Engineering Journal, 2025)
We present a new authentication protocol developed to meet the aforementioned issues of IoMT environments. The proposed protocol incorporates lightweight cryptography and physical unclonable functions (PUFs), ensuring secure and efficient data exchanges within the IoMT environment after completing the authentication and session key establishment process. The inclusion of PUFs enhances the protection against insider threats by dynamically generating persistent keys directly from the medical server's hardware, eliminating the risk of storing them in plaintext within databases. Moreover, the application of lightweight cryptographic techniques reduces latency, making the protocol pertinent for real-time medical procedures. Additionally, it ensures that messages sent during the proposed protocol's authentication phase are anonymous and untraceable. Through thorough analysis, we illustrate that the proposed protocol significantly strengthens the security and performance of the IoMT environment, establishing it as a robust and scalable solution for the next generation of healthcare infrastructures.